Explorative behaviour is not associated with metabolism in the European Pied Flycatcher Ficedula hypoleuca - Oona Poranen; Suvi Ruuskanen (Blackwell Publishing Ltd, 2025)
The pace‐of‐life syndrome hypothesis (POLS) represents an attractive theoretical framework suggesting that physiological and behavioural traits have evolved together with environmental conditions and life‐history strategies. POLS predicts that metabolic differences covary with behavioural variation such that high metabolic rate is associated with risk‐prone behaviour and a faster pace‐of‐life, whereas a low metabolic rate is associated with risk‐averse behaviour and a slower pace‐of‐life. We tested the POLS hypothesis in captive European Pied Flycatchers during their first year by examining the relationship between explorative behaviour and basal metabolic rate. Our results are inconsistent with POLS. The positive association of explorative behaviour with basal metabolic rate was not recovered for either sex, possibly due to foraging conditions in the aviaries where control and trial groups were fed twice a day, the birds' young age, developmental plasticity, or a non‐existent syndrome.